THE IMPORTANCE OF FUTURE LEGAL SPECIALISTS IN IMPROVING THE STATE GOVERNANCE INDEX - Abdutolipov Muzaffar Gofurovich (Scholar Express Journals, 2025)
The article highlights that competent personnel are a key indicator in improving the transparency of public administration and raising a country’s position in international ratings. It analyzes the significance of modern approaches in training future legal specialists and the practical results of educational projects.
Keywords: Public administration; global development; rule of law